Response of some mango-infesting fruit flies to aqueous solutions of the basil plant Ocimum tenuiflorum L - Niassy, Saliou; Mohamed, Samira Abuelgasim; Cheseto, Xavier; Omuse, Evanson Rigan; Ochola, John Bwire; Khamis, Fathiya Mbarak; Badji, Boubacar; Ndlela, Sheppard; Ombura, Levi; Okun, Noelah Leah; Kupesa, David Mfuti; Dubois, Thomas; et al. (Frontiers in Horticulture, 2023)
Introduction Horticulture is an important sub-sector for many African countries. Tephritid fruit flies continue to cause serious direct and indirect damage to the sub-sector. The male annihilation technique (MAT) using methyl eugenol (ME) is among the most revered techniques in fruit fly management. However, ME-based lures are only available to some farmers in Africa. Several basils of the genus Ocimum produce ME. Methods In laboratory experiments, we used a dual choice olfactometer to assess the attraction of adult oriental fruit fly Bactrocera dorsalis to intact plants, 100 µL commercial methyl eugenol (ME) (positive control), 10 mg/mL of O. tenuiflorum aqueous extract (Otae), and a negative control (blank). Large arena experiments were conducted to compare the responses of four fruit fly species of economic importance in Africa to Otae-baited traps. Results In dual choice olfactometer assay, more B. dorsalis males (78.6%) than females (23.8%) were attracted to Otae. Most B. dorsalis males were attracted to the positive control (90.5%) and 10 mg/mL Otae (88.5%) compared to the whole plant (84.0%). In large arena experiments, Otae attracted the most B. dorsalis males (47.7%), followed by Zeugodacus cucurbitae males (25.1%), while males of Ceratitis species were the least attracted. The analysis of headspace volatiles from aerial plants, Otae and essential oil using gas chromatography-mass spectrometry detected 97 compounds. The intact plant without flowers, intact plant with flowers, Otae, and the O. tenuiflorum essential oil contributed 76, 62, 33 and 28 compounds, respectively. ME comprised the top three most abundant compounds, especially in the essential oil. Discussion Our study confirms the potential of O. tenuiflorum as a source of ME for tephritid fruit fly integrated management in Africa. Otae, a readily available alternative to commercial ME, can be used to develop fruit fly-baited traps, particularly for smallholder farmers.